What Is an Identical Translation? The Legacy of Goethe's Discussion in the West-östlicher Divan. (1st September 2020) - Beebee, Thomas O.
ABSTRACT: Goethe's brief discussion of translation in the Noten and Abhandlungen to the Divan has been one of the most widely read and interpreted parts of its prose commentary section. Goethe's three epochs of translation culminate in translations that are 'identisch' with the original. This essay explains what identicality can mean in the realm of translation, including how some of Goethe's major interpreters in translation studies have understood his comments.